2022
DOI: 10.21203/rs.3.rs-2341238/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biosynthesis approach of zinc oxide nanoparticles for aqueous phosphorous removal: physicochemical properties and antibacterial activities

Abstract: In this study, phosphorus (PO43–-P) is removed from water samples using zinc oxide nanoparticles (ZnO NPs). These nanoparticles are produced easily, quickly, and sustainably using Onion extracts (Allium cepa) at average crystallite size 8.13 nm using Debye-Scherrer equation in hexagonal wurtzite phase. The bio-synthesis ZnO NPs characterization and investigation were conducted. With an initial concentration of 250 mg/L of P, the effects of the adsorbent dose, pH, contact time, and temperature were examined. At… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…At 60 °C, the material was dried for 6 hrs. ZnO NPs separated precipitate was calcined for 2 hrs at 400 o C 25 .…”
Section: Green Synthesis Of Zno Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 60 °C, the material was dried for 6 hrs. ZnO NPs separated precipitate was calcined for 2 hrs at 400 o C 25 .…”
Section: Green Synthesis Of Zno Npsmentioning
confidence: 99%
“…The sample created using onion extract has pure ZnO phases, according to the energy dispersive spectra of the samples obtained from the SEM-EDX analysis. Analysis of the sample showed that they had wt% of the elements 71.33% Zn and 15.13 O, indicating that the produced ZnO NPs are in their purest form 25,46 .…”
Section: Morphology Analysis (Sem Tem and Edx Analyses)mentioning
confidence: 99%